Extracts of Polypore Mushroom Mycelia Reduce Viruses in Honey Bees. Issue 1 (December 2018) - Stamets, Paul; Naeger, Nicholas; Evans, Jay; Han, Jennifer; Hopkins, Brandon; Lopez, Dawn; Moershel, Henry; Nally, Regan; Sumerlin, David; Taylor, Alex; Carris, Lori; Sheppard, Walter
Abstract Waves of highly infectious viruses sweeping through global honey bee populations have contributed to recent declines in honey bee health. Bees have been observed foraging on mushroom mycelium, suggesting that they may be deriving medicinal or nutritional value from fungi. Fungi are known to produce a wide array of chemicals with antimicrobial activity, including compounds active against bacteria, other fungi, or viruses. We tested extracts from the mycelium of multiple polypore fungal species known to have antiviral properties. Extracts from amadou (Fomes ) and reishi (Ganoderma ) fungi reduced the levels of honey bee deformed wing virus (DWV) and Lake Sinai virus (LSV) in a dose-dependent manner. In field trials, colonies fedGanoderma resinaceum extract exhibited a 79-fold reduction in DWV and a 45, 000-fold reduction in LSV compared to control colonies. These findings indicate honey bees may gain health benefits from fungi and their antimicrobial compounds.